Optimal Decision-Making in Life Insurance Purchasing Behaviour in Malaysia - Jia Wei, Gan (UNIVERSITI MALAYSIA SARAWAK, 2025)
In Malaysia, the life insurance penetration rate is still low compared to nations like Taiwan, Japan, and Thailand, indicating a gap in coverage and financial preparedness. This study examined the moderating role of hyperbolic discounting on optimal decisions of life insurance purchasing behaviour and investigated the influences of attitude, subjective norm, perceived behavioural control, financial literacy, and perceived risk through the mediating role of intention. The theory of planned behaviour with the hyperbolic discounting model has been integrated in this study. This study utilised an online survey-based methodology, collecting data from Malaysian households using convenience and snowball sampling. The survey yielded 304 responses and was selected for analysis through structural equation modelling. The results discovered that subjective norms, perceived behavioural control, financial literacy, and perceived risk influenced optimal decisions of life insurance purchasing behaviour. There was a mediating role of intention for the relationships between attitude towards life insurance, perceived behavioural control, financial literacy, and optimal decisions of life insurance purchasing behaviour; however, hyperbolic discounting did not demonstrate a moderating effect. This study highlights the need for targeted interventions such as financial education, personalised advice, and social influence to improve consumers' optimal decisions. It also emphasises the importance of information transparency, streamlined offerings, and collaborations among government, financial institutions, and insurers to improve accessibility and bridge the gap in coverage and financial preparedness.